2016
DOI: 10.1080/13548506.2016.1146405
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of mindfulness-based stress reduction (MBSR) on posttraumatic growth of Chinese breast cancer survivors

Abstract: Breast cancer (BC) patients in China suffered from a variety of psychology stress such as perceived stress and anxiety, posttraumatic growth (PTG) as a positive factor could promote their psychology health and quality of life. This study aimed to investigate the efficacy of mindfulness-based stress reduction (MBSR) on promoting PTG, decreasing perceived stress and anxiety of Chinese BC patients. A randomized controlled trial of 60 BC patients (Stages I-III) was conducted. They were randomly divided to the 8-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 30 publications
3
71
0
Order By: Relevance
“…Twelve of 30 studies (40%) failed to identify a primary aim and reported multiple outcomes . Of the 18 (60%) studies identifying a single primary aim and outcome measure, 2 aimed to reduce anxiety/depression or improve mood, 2 to improve quality of life, 3 focused on perceived stress/distress, 7 targeted physical symptomology such as fatigue, insomnia, or sleep disturbance, 2 physiological responses, 1 improve cognition, and 1 improve post traumatic growth . All but one study with a defined primary outcome included validated outcome measures, and in all these studies there was concordance between the identified primary aim and measures.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Twelve of 30 studies (40%) failed to identify a primary aim and reported multiple outcomes . Of the 18 (60%) studies identifying a single primary aim and outcome measure, 2 aimed to reduce anxiety/depression or improve mood, 2 to improve quality of life, 3 focused on perceived stress/distress, 7 targeted physical symptomology such as fatigue, insomnia, or sleep disturbance, 2 physiological responses, 1 improve cognition, and 1 improve post traumatic growth . All but one study with a defined primary outcome included validated outcome measures, and in all these studies there was concordance between the identified primary aim and measures.…”
Section: Resultsmentioning
confidence: 98%
“…Studies were assessed for inclusion of rationale for therapeutic benefits of mindfulness to the target population. Fourteen studies provided a full justification, 9 a partial rationale for the potential benefits of mindfulness in their population, 4 studies mentioned but did not justify population, while 3 provided no rationale . Mean score for population selection justification was 2.13 (SD 1.0; range 0–3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Step (Zhang et al, 2017). Considering this outcome, mindfulness-based intervention could help women with breast cancer to reduce their stress and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Mindfulnessbased practices increase efficiency and reduces stress [7]. Focus, clarity, and the quality of everything we attend to improves when we immerse ourselves in what is now.…”
Section: Your Best Lifementioning
confidence: 99%